(untitled) (Pain medicine, 2020)
PAIN is a psychophysiological reaction of an organism that occurs with severe irritation of the sensitive nerve endings embedded in organs and tissues. And also pain is the body’s protective reaction. It is signaling about a discomfort and triggers an appropriate response by the body to eliminate the cause of the pain. Pain is one of the earliest symptoms of some diseases [84]. ITCHING – an unpleasant sensation of irritation, heartburn and tingling in any area of the skin caused by various factors (exposure to chemicals, bacteria, parasites). This feeling is often manifested by the urgent need to rub or scratch some areas of the skin (or mucous membrane) [85]. When considering the pathogenesis of these concepts, a sufficiently large resemblance to the realization of mechanisms of origin, or a certain identity thereof is revealed. The question naturally arises whether itching is an early manifestation of pain, especially in those groups of diseases that are not characterized by pain. Pathology of the hematopoietic system is not accompanied by a symptom such as pain. But for conditions such as iron overload, iron deficiency or polycythemia, itching is a clear symptom. The unknown etiology of chronic itching of the skin is indicative of histological examination of the skin in order to exclude skin lymphoma. One of the least understood mechanisms of itching is itching associated with malignant solid tumors. What pain that itching is a subjective sensation that can have an acute or chronic course, a clear intensity and a very significant impact on quality of life, especially in the case of comorbidity. In addition, the question arises whether itching is an early manifestation of pain, especially in those groups of diseases that are not characterized by pain. How can a doctor manage itching effectively to prevent complications? To these and other questions, we have attempted to systematize the manifestations of itching in pathologies of organs and systems that are not traditionally accompanied by pain.